2022
DOI: 10.17645/mac.v10i3.5468
|View full text |Cite
|
Sign up to set email alerts
|

WhatsApp as a Tool for Researching the Everyday Lives of Venezuelan Refugees Settling in Brazil

Abstract: In this article, we explore the role that WhatsApp can play as a research tool for investigating the experiences of settling refugees. Messaging apps can help researchers collect data about people’s everyday lives while also providing insights into processes that are difficult to study as they happen. The communicative affordances of messaging apps also facilitate spontaneous interactions in research and the flexibility needed when working with mobile groups of people, such as refugees. We build on our experie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 27 publications
0
6
0
Order By: Relevance
“…Our formative focus groups indicated that MNP in Costa Rica can typically access both. Nevertheless, studies of Latin American MNP who have migrated to other countries in the region suggest that the most socioeconomically disadvantaged MNP and those living in rural areas may have a more difficult time accessing either [73][74][75]. It therefore remains possible that some groups of MNP are underrepresented in our study.…”
Section: Plos Onementioning
confidence: 95%
“…Our formative focus groups indicated that MNP in Costa Rica can typically access both. Nevertheless, studies of Latin American MNP who have migrated to other countries in the region suggest that the most socioeconomically disadvantaged MNP and those living in rural areas may have a more difficult time accessing either [73][74][75]. It therefore remains possible that some groups of MNP are underrepresented in our study.…”
Section: Plos Onementioning
confidence: 95%
“…While a number of studies focus on using digital technology to study phenomena or research subjects’ experience of online/offline interactions (e.g. Alencar and Carmago, 2022), few exist on the intricacies of conducting hybrid ethnography. Those that do, focus mainly on methodological tools such as how to gain access and conduct research by combining physical and digital presence (e.g.…”
Section: Hybrid Ethnographymentioning
confidence: 99%
“…Mobiles phones have become integrated into the dynamic processes of global migration in recent years. Migrants use these technologies to, among other things, facilitate the migration journey, save and share important documents, maintain relationships across distances, call for search and rescue services, send and receive money, access medical services, obtain food rations, apply for or renew visa statuses, and learn the language of their host countries [1][2][3]21]. For asylum seekers in particular, smartphones may be used to store or retrieve evidence that substantiates their asylum claims with the understanding that paper evidence may be lost, destroyed, or stolen along the migrant journey.…”
Section: Migrants' Smartphones As Mobile Bordersmentioning
confidence: 99%
“…Migration and migration controls are becoming increasingly mediated through technology. Existing research has examined how migrants use mobile phones to facilitate the migration journey, save and share important documents, maintain relationships across distances, call for search and rescue services, send and receive money, access medical services, obtain food rations, apply for or renew visa statuses, document abusive state practices, and learn the language of their host country [1][2][3][4][5][6][7]. Governments, too, have incorporated technology into migration controls by deploying biometric screening at borders, developing complex regimes of surveillance, and incorporating algorithms and artificial intelligence into decision-making processes [8][9][10][11][12][13][14][15][16].…”
Section: Introductionmentioning
confidence: 99%